2021
DOI: 10.3389/fvets.2021.676774
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intra-Articular Amikacin Administration in an Equine Non-inflammatory Joint Model to Identify Effective Bactericidal Concentrations While Minimizing Cytotoxicity

Abstract: Septic arthritis causes significant morbidity and mortality in veterinary and human clinical practice and is increasingly complicated by multidrug-resistant infections. Intra-articular (IA) antibiotic administration achieves high local drug concentrations but is considered off-label usage, and appropriate doses have not been defined. Using an equine joint model, we investigated the effects of amikacin injected at three different doses (500, 125, and 31.25 mg) on the immune and cartilage responses in tibiotarsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…These findings might be partly due to the frequent use of local administration of antimicrobials, either intrasynovial or via regional limb perfusion in our study. Local delivery of antimicrobials is increasingly used and is effective in achieving high concentrations in the specific region, while decreasing the treatment cost and the potential side effects of systemic administration [ 33 , 34 , 35 , 36 ]. There has been considerable research on regional limb perfusion protocols in experimental settings [ 37 , 38 , 39 , 40 ] but very limited reports on frequency and efficacy of local antimicrobial administration in naturally occurring traumatic injuries and in SI in horses [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings might be partly due to the frequent use of local administration of antimicrobials, either intrasynovial or via regional limb perfusion in our study. Local delivery of antimicrobials is increasingly used and is effective in achieving high concentrations in the specific region, while decreasing the treatment cost and the potential side effects of systemic administration [ 33 , 34 , 35 , 36 ]. There has been considerable research on regional limb perfusion protocols in experimental settings [ 37 , 38 , 39 , 40 ] but very limited reports on frequency and efficacy of local antimicrobial administration in naturally occurring traumatic injuries and in SI in horses [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its intended purpose is to ensure local concentrations of antibiotic exceed minimum inhibitory concentrations in the joint for a period of time. Amikacin has been shown to exceed minimum inhibitory concentrations for over 24 hours when used intra‐articularly in horses 27 . However, one study in calves showed no difference in clinical outcome if gentamicin was administered intra‐articularly in addition to systemic use 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Amikacin has been shown to exceed minimum inhibitory concentrations for over 24 hours when used intra-articularly in horses. 27 However, one study in calves showed no difference in clinical outcome if gentamicin was administered intra-articularly in addition to systemic use. 28 Gentamicin-impregnated implants exist that can be placed in the joint and allow sustained release.…”
Section: Antibiotic Selectionmentioning
confidence: 99%
“…For example, injection of 150 mg of gentamicin has been shown to yield 1000-fold higher concentrations in synovial fluid when compared to systemic administration of a 6.6 mg/kg bwt IV dose, and concentrations remain above the MIC for many equine pathogens for more than 24 h (Lloyd et al, 1990). Repeated intrasynovial injections can be performed easily on most horses and should be considered in cases of synovial sepsis (Pezzanite, Chow, Hendrickson, et al, 2021).…”
Section: Tre Atmentmentioning
confidence: 99%